Health Transition Probability and Long-Term Care Cost Estimation. (22nd April 2022) - Cui, Xiaodong; Duan, Xuexiang; Chang, Ching-Ter; Jiang, Shuhua
Abstract : The cost of long-term care (LTC) is one of the huge financial risks faced by the elderly and also is a significant challenge to the social security system. This article establishes a piecewise constant Markov model to estimate the dynamic health transition probability and based on actuarial theory to calculate the long-term care cost, in contrast to the static or nontransferable state hypotheses in traditional models. Using the Chinese Longitudinal Healthy Longevity Survey, this article found that the average cost of LTC for the elderly varies greatly due to gender and health conditions, the cost for women may increase by up to 75% compared to that for men, and the cost for unhealthy elderly may more than double compared to that for healthy elderly. Furthermore, if LTC is included in the medical insurance system, in theory, women's average pay price will be more than twice that of men.